(untitled) - Majercak, Jozef; Plevko, Juraj (Doprava a spoje, 2012)
Calculations have shown that the process is very sensitive to the fairness of the input information, which significantly affects the degree of uncertainty (entropy) and thus the weight of the selected key evaluating indicators . This increased sensitivity of this method is closest to the objective evaluation of the weights of key evaluating indicators in the event that we do not know the priority of selected key evaluating indicators.